PERAN MEDIA SOSIAL SEBAGAI STRATEGI BRANDING PRODUK KULINER INOVATIF - Rizka Maydikta; Yashinta Zahra Alfitri; Karyadi Hidayat (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
The rapid advancement of digital technology has positioned social media as a key medium for marketing and brand development, particularly within the continuously evolving culinary industry. This study aims to analyze the role of social media in strengthening branding strategies for innovative culinary products through promotional activities and interactive communication with consumers. The research employs a qualitative descriptive approach, utilizing literature analysis and observations of promotional practices across platforms such as Instagram, TikTok, and Facebook. The findings indicate that the effective use of social media enhances brand awareness, broadens market reach, and fosters closer relationships between producers and consumers. Furthermore, consistent and creative content management significantly contributes to the establishment of a positive brand image and consumer loyalty. Therefore, social media serves a strategic function as an effective medium to reinforce the visibility and competitiveness of innovative culinary products in the digital era.Keywords: social media, branding strategy, innovative culinary, digital promotion, marketing